苏轼与刘因“和陶诗”之比较 = Comparison between Su Shi and Liu Yins’ responsorial poetry to Tao Yuan Ming - 蔡佳敏 Cai, Jiamin (2012)
“和陶诗”，指和答东晋诗人陶渊明诗作的诗。陶渊明“性本爱丘山”的志趣与“终身与世辞”的选择，使之被称为“古今隐逸诗人之宗”，成为后世失意士人所普遍追和的对象。首位追和陶渊明诗歌者，可追溯至北宋著名文人苏轼。其“和陶诗”也掀起了后人的和陶风气，其中包括元初著名诗人刘因。纵观苏轼与刘因的“和陶诗”，可窥见苏轼的“静而不隐”与刘因的“隐而不静”。苏轼虽不曾辞官归隐，却于“和陶诗”表露其安时处顺之态，故谓之“静而不隐”。反观刘因，虽曾两度推辞征召，却于“和陶诗”展露其欲有所为之志，故谓之“隐而不静”。两人由和陶表达了复杂的仕隐情结，其中“静”与“隐”与陶渊明原诗切合，而“不隐”与“不静”则与原诗相异。这种“既同于渊明，又异于渊明”的创作心理，是由和诗“先阅读，后创作”的特质所引起的和诗诗人对原诗的接受与超越所致。本研究将从“和陶诗”对诗人生活与思想两方面的体现，比较苏轼与刘因的仕隐情结。在此基础上，拟以姚斯接受美学的期待视界概念分析诗人追和陶诗的创作心理，从和诗的特质观察苏轼“静而不隐”与刘因“隐而不静”的现象，以期为“和陶诗”研究提供另一思路。A plentiful number of poets have composed abundant responsorial poems to Tao Yuan Ming, who is recognised for his seclusion image. Su Shi from the Song dynasty was the first known poet to have initiated the creation of responsorial poems to Tao Yuan Ming. His practice also triggered the trend for such poems to be greatly produced over the years, and Liu Yin from the Yuan dynasty was one of the many influenced. Having a deep look into their responsorial poems, Su Shi displayed tranquil despite not entering seclusion, while Liu Yin exhibited his careerism despite entering seclusion. Su Shis’ tranquil and Liu Yins’ seclusion correspond to Tao Yuan Ming’s original poems; while Su Shis’ non-seclusion and Liu Yins’ careerism differ from Tao Yuan Ming’s original poems. These contradictions actually portray the characteristic of responsorial poetry, which is the involvement of the process of reading before creating, resulting in poets accepting, as well as going beyond the original poems. This paper aims at providing a comprehensive study of Su Shi and Liu Yins’ responsorial poems to Tao Yuan Ming, in terms of how the poems illustrate both the livelihood and the mentality of the poets. Upon which, the Horizons of Expectations concept from the Aesthetics of Reception theory by Jauss will be employed to explore the underlying factors contributing to the poets’ complexity in mind while creating the responsorial poems, with the intention of providing a new methodology in the research of responsorial poetry to Tao Yuan Ming.